Chinese and Siamese cultures in malay muslims environment - Zuriati Mohd Rashid; Nur Azuki Yusuff (2014)
The main objective of this study is to explore the quality of religious understanding between Muslims and Buddhists in Kampung Tendong. The researcher prepared some relevant indicators to measure the quality. These indicators include intra-religious understandings and inter-religious understandings. Using a convenience sampling technique, a total of one hundred and forty (140) respondents were drawn from Muslims and Buddhists of Kampong Tendong, Pasir Mas, Kelantan. The sample size together with the above-mentioned indicators showed that the quality of interaction based on frequency is below average (i.e., 42.59%). The results show universal values of the two religions, namely Islam and Buddhism that bind people together. On the other hand, the discouraging factor of interaction among the residents of Kampung Tendong was that trivial issues of religious differences. Therefore, the significance of the study lies mainly in showing the level of religious understanding between Muslims and Buddhists in Kampung Tendong. This result is essential to the policy-makers to develop a better pattern of inter-racial interaction in a remote area of Peninsular Malaysia. The study finally discusses the need for broader and more comprehensive research in this area.